Analysis of polyethylene glycol (PEG) fusion in cultured neuroblastoma cells via flow cytometry: Techniques & optimization. (February 2017) - Hoffman, Ashley N.; Bamba, Ravinder; Pollins, Alonda C.; Thayer, Wesley P.
Highlights: PEG fusion is a technique for peripheral nerve repair. Flow cytometry is proposed as a method for assessment of PEG fusion. Results indicate increasing cell fusion with increasing PEG concentration. Cell viability decreases with increasing PEG concentration. Abstract: Polyethylene glycol (PEG) has long been used as a membrane fusogen, but recently it has been adopted as a technique for peripheral nerve repair. Vertebrate models using PEG fusion have shown improved outcomes when PEG is applied during repair of severed peripheral nerves. The cellular mechanism of PEG fusion in the peripheral nerve repair model has not previously been assessed via flow cytometry. PEG fusion was assessed in this experiment by dying B35 rat neuroblastoma cells with different color fluorescent labels. The different color cells were combined and PEG was applied in concentrations of 50%, 75% and 100%. The amount of cell fusion was assessed via flow cytometry as the percentage of double positive cells. Results showed increasing fusion and decreasing viability with increasing concentrations of PEG.